2019
DOI: 10.1016/j.cegh.2019.04.005
|View full text |Cite
|
Sign up to set email alerts
|

A spatial analysis of childhood stunting and its contextual correlates in India

Abstract: Introduction: Despite various programmes aiming to improve the nutritional status of children, nearly 38% of children under age five are still stunted in India, and there is huge spatial variation across the states. Objectives: The present study first examines the spatial clustering of childhood stunting and then investigates the contextual determinants including meteorological factors, poverty and crop production affecting childhood stunting. Methods: The percentage of stunted children under 5 years of age is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 22 publications
4
34
1
Order By: Relevance
“…The spatial autocorrelation analysis Fig. 2, Table 1 revealed that childhood stunting and severe stunting had a high spatial dependency (respectively, Moran's I: 0.55 and 0.40) in agreement with studies done in India 38,39 . The LISA results Fig.…”
Section: Discussionsupporting
confidence: 84%
“…The spatial autocorrelation analysis Fig. 2, Table 1 revealed that childhood stunting and severe stunting had a high spatial dependency (respectively, Moran's I: 0.55 and 0.40) in agreement with studies done in India 38,39 . The LISA results Fig.…”
Section: Discussionsupporting
confidence: 84%
“…These regions occupy intermediate level of aggregation between a district and a state and interregion variation within the same state is an important feature to be noted. Few recent studies [38][39][40][41] have explored spatial clustering of key malnutrition indicators such as stunting, anaemia, low birth weight, etc. and its correlates in India.…”
Section: Discussionmentioning
confidence: 99%
“…As in the global literature [8], the role of contextual factors is much less studied than that of proximal factors of CS in India. We came across just four articles that assessed the role of contextual factors such as climatic conditions, food production, access to healthcare facilities, and macroeconomic development [21][22][23][24]. These studies have by and large explored the role of selected contextual factors in isolation; moreover, the analysis presented in some of these studies was limited to small geographies.…”
Section: Introductionmentioning
confidence: 99%